HISTORY LEARNING ON THE APPROACH OF MULTICULTURAL AND LOCAL, NATIONAL, GLOBAL HISTORY PERSPECTIVE FOR NATIONAL INTEGRATION : A Quasi-Experimental Study on Senior High School Student in Bandung City - Supardan, Dadang (2005)
This study was motivated by the writer's concern on the accumulating phenomena of national disintegration in many parts of Indonesian territory, and this situation influenced the restlessness and instability among the young generation, in this case the senior highschool student, regarding to their identity and nationality. The result of th orientation phase in this research showed, that history teaching and learning in the hihgschools were not able to imprint strong historical awareness and sense of belonging to the country to support the national integration among the students. The assumptions were the weakness among the majority of history teachers in their professional skills, especially in their selecting the subject, choosing the teaching and learning strategies, and in taking up the approaches. Several problems examined in this study revealed that in classes, history was still presented in the conventional way, where the students were lectured on factual feature of history (time concept, actors, and sequence of events). The political aspect of history was the main portion taught during the lessons, without touching the pluralistic social and cultural characteristic of the Indonesian society. On the other hand, the new learning in history, which was called the New History, opened multidisciplinary approach where sociology and anthropology contributed to the student's efforts of searching for their ethnic and cultural roots inside the Indonesian nationality. By knowing and comprehending other ethnic groups and other cultures, the students learned the danger of stereotyping, social prejudice, and exclusion which threatened the principle of living together harmoniously towards national integration. Based on the introductory statement above, the reseach problem of this study would be stated as followed: "Are there any significant differences in students' awareness in history before and after the teaching and learning of history according to the multiculturalism in local, national, global perspectives ?" The methodology used in this study was both quatitative and qualitative paradigms, with quasi-experimental design and data compiled by interview technique among 258 senior highschool students in Bandung municipality. The research findings are firstly, that the influence of multicultural approach in teaching and learning history towards the acquiring of inter-ethnic relations and national solidarity are significant. Second, that the influence of local history teaching and learning to aquire good inter-ethnic relations is significant, while the contribution to national solidarity is positively significant. Third, that the influence of national history teaching and learning towards inter-ethnic relations is significant, but insignificant to building national solidarity. Forth, that the influence of global history teaching and learning towards inter-ethnic relations and national solidarity are quite significant; and lastly, that the influence of teaching and learning inter-ethnic relations towards building national solidarity is significant.